Palestine, Israel and the U.S. empire - Becker, Richard (1804 Books, 2023)
"A sharp analysis of the struggle for Palestine gets and update following the events of October 7, 2023. Palestine, Israel, and U.S. Empire is an essential book for the current moement. Taking a firm anti-Zionist perspective on the history of Palestine and Israel, it traces the movements of resisteance from British colonialism to the fight back in Gaza and the West Bank today." --Provided by publisher